2013
DOI: 10.2106/jbjs.l.01607
|View full text |Cite
|
Sign up to set email alerts
|

Effect and Possible Mechanism of Muscle-Splitting Approach on Multifidus Muscle Injury and Atrophy After Posterior Lumbar Spine Surgery

Abstract: This study provides a basis for the prevention of multifidus muscle injury and atrophy after posterior lumbar surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
70
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 27 publications
1
70
0
3
Order By: Relevance
“…At present, the commonly used surgical procedure is open lumbar posterior nerve root decompression and exploration 2. However, the traditional open surgery is associated with large incision, requiring extensive stripping of the paravertebral soft tissues, heavy trauma, and a large amount of blood loss, which usually leads to denervation of muscle and atrophy,57 and in addition, the patients suffer from long-term postoperative lumbodorsal muscle pain. These postoperative complications seriously affect the clinical recovery and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the commonly used surgical procedure is open lumbar posterior nerve root decompression and exploration 2. However, the traditional open surgery is associated with large incision, requiring extensive stripping of the paravertebral soft tissues, heavy trauma, and a large amount of blood loss, which usually leads to denervation of muscle and atrophy,57 and in addition, the patients suffer from long-term postoperative lumbodorsal muscle pain. These postoperative complications seriously affect the clinical recovery and patient satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Postoperative residual lumbago and backache are the disadvantages of traditional PLIF surgery 2. Our data showed that MIS-TLIF reduced the back pain VAS scores 3 months after surgery in comparison with the PLIF.…”
Section: Discussionmentioning
confidence: 53%
“…However, the traditional PLIF requires large incision, extensive dissection of paraspinal soft tissue trauma and blood loss, which inevitably contributes to muscle denervation and atrophy 1. Moreover, because of the removal of the bilateral vertebral plate, spinous process and ligament, the lumbar spine rear structural damage is large, and this surgery inevitably leads to postoperative adhesions, dural nerve roots and long-term low back muscle pain 2. All these later complications seriously affect the clinical efficacy and decrease the patients’ quality of life.…”
Section: Introductionmentioning
confidence: 99%
“…There are many muscles at the posterior the lumbar spine that support our body, the back muscle injury is one of the main problems of traditional open posterior lumbar surgery (26,27). Hu et al (13) reported that the traditional powerful muscle retraction will not only cause multifidus injury, but also cause long-term multifidus atrophy after posterior lumbar surgery.…”
Section: Discussionmentioning
confidence: 99%